Human resources requirements for highly active antiretroviral therapy scale-up in Malawi - Rudatsikira Emmanuel; Siziya Seter; Chipeta John; Muula Adamson S; Mataya Ronald H; Kataika Edward (BMC, 2007)
Abstract Background Twelve percent of the adult population in Malawi is estimated to be HIV infected. About 15% to 20% of these are in need of life saving antiretroviral therapy. The country has a public sector-led antiretroviral treatment program both in the private and public health sectors. Estimation of the clinical human resources needs is required to inform the planning and distribution of health professionals. Methods We obtained data on the total number of patients on highly active antiretroviral treatment program from the Malawi National AIDS Commission and Ministry of Health, HIV Unit, and the number of registered health professionals from the relevant regulatory bodies. We also estimated number of health professionals required to deliver highly active antiretroviral therapy (HAART) using estimates of human resources from the literature. We also obtained data from the Ministry of Health on the actual number of nurses, clinical officers and medical doctors providing services in HAART clinics. We then made comparisons between the human resources situation on the ground and the theoretical estimates based on explicit assumptions. Results There were 610 clinicians (396 clinical officers and 214 physicians), 44 pharmacists and 98 pharmacy technicians and 7264 nurses registered in Malawi. At the end of March 2007 there were 85 clinical officer and physician full-time equivalents (FTEs) and 91 nurse FTEs providing HAART to 95,674 patients. The human resources used for the delivery of HAART comprised 13.9% of all clinical officers and physicians and 1.1% of all nurses. Using the estimated numbers of health professionals from the literature required 15.7-31.4% of all physicians and clinical officers, 66.5-199.3% of all pharmacists and pharmacy technicians and 2.6 to 9.2% of all the available nurses. To provide HAART to all the 170,000 HIV infected persons estimated as clinically eligible would require 4.7% to 16.4% of the total number of nurses, 118.1% to 354.2% of all the available pharmacists and pharmacy technicians and 27.9% to 55.7% of all clinical officers and physicians. The actual number of health professionals working in the delivery of HAART in the clinics represented 44% to 88.8% (for clinical officers and medical doctors) and 13.6% and 47.6% (for nurses), of what would have been needed based on the literature estimation. Conclusion HAART provision is a labour intensive exercise. Although these data are insufficient to determine whether HAART scale-up has resulted in the weakening or strengthening of the health systems in Malawi, the human resources requirements for HAART scale-up are significant. Malawi is using far less human resources than would be estimated based on the literature from other settings. The impact of HAART scale-up on the overall delivery of health services should be assessed.